UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR IPS MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) - Rohaeni, Ida; H. Matsum, Junaidi; Asriati, Nuraini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstract : Efforts to Improve Learning Outcomes Activities and IPS Through Cooperative Learning Model Implementation Group invertigation type (GI) In Grade VIII Junior. Action research aims to assist teachers in improving students' learning activities and learning outcomes of students using cooperative learning model type group investigation (GI) on the subjects of social.Based on data from prior studies of student learning activities of students who belong to the category known active and highly active only amounted to 6 students or 20% of the number of students., After the implementation of the first cycle gained increasing student learning activities into 9 students were classified as active and very active, and in the second cycle increased to 13 students or 65%. Thus the hypothesis was formulated action accepted as true that efforts to improve the activity and results belajarIPS through the implementation of cooperative learning model type Group intesvigasi (GI). Keywords : Cooperative Learning Model, Group Investigation (GI). Abstrak : Upaya Meningkatkan Aktivitas dan Hasil Belajar IPS Melalui Model Pembelajaran Kooperatif type Group invertigation (GI). Penelitian tindakan kelas ini bertujuan untuk membantu guru dalam meningkatkan aktivitas belajar siswa dan hasil belajar siswa dengan menggunakan model pembelajaran kooperatif tipe group investigation (GI). Berdasarkan data sebelum penelitian aktivitas belajar siswa diketahui siswa yang tergolong kategori aktif dan sangat aktif hanya berjumlah 6 orang siswa atau 20 % dari jumlah siswa., setelah pelaksanaan siklus pertama diperoleh peningkatan aktivitas belajar siswa menjadi 9 orang siswa yang tergolong aktif dan sangat aktif, dan pada siklus kedua meningkat menjadi 13 orang siswa atau 65 %. Dengan demikian hipotesis tindakan yang telah dirumuskan diterima kebenarannya yaitu upaya meningkatkan aktivitas dan hasil belajar IPS melalui penerapan model pembelajaran kooperatif tipe Group intesvigasi (GI). Kata Kunci : Model Pembelajaran Kooperatif, Group Investigation (GI).